Effect of foliar nutrition on yield, nitrogen uptake and quality of soyabean under rainfed condition - Abhinandan Singh; Anjali Ram Kishor Varma; Utkarsh Singh; Muyeen I Nargund; Mayank Mani Tripathi (Annals of Agricultural Research, 2024)
During the Kharif season of 2022, a field experiment on the effects of foliar nutritionon the yield and nitrogen uptake by soybean under rainfed condition was carried out at the Crop Research Centre, School of Agriculture, ITM University Gwalior (M.P.). The field experiment was laid out in a randomized block design with 10 treatment combinations and replicated thrice. The treatments are, RDF (100%)@ at the time of sowing, NPK (19:19:19) @ 0.5% at 40 DAS, NPK (19:19:19) @ 1.0% at 40 DAS, NPK (19:19:19) @ 1.5% at 40 DAS, NPK (13:0:45) @ 0.5% at 60 DAS, NPK (13:0:45) @ 1.0% at 60 DAS, NPK (13:0:45) @ 1.5% at 60 DAS, NPK (19:19:19) @ 0.5% at 40 DAS + NPK (13:0:45) @ 0.5% at 60 DAS, NPK (19:19:19) @ 1.5% at 40 DAS + NPK (13:0:45) @1.5 % at 60 DAS and RDF (20:60:20) + Sulphur and one absolute control. The experimental findings showed that the higher grain yield (2153.37 ka ha-1), stover yield(3253.23 ka ha-1) and biological yield (5409.09 ka ha-1). were obtained by applying NPK (19:19:19) @ 1.5% at 20 DAS + NPK (13:0:45) @ 1.5% at 40 DAS. The uptake of nitrogen [in the seed (150.58 kg ha-1) and stover (44.38 kg ha-1)] by the soybean plant was found to be significantly enhanced by increasing the quantities of foliar fertilizers among all the treatments. The soybean plant’s oil (22.17%) and protein (43.75%) contents were also greatly raised. Applying NPK (19:19:19) @ 1.5% at 20 DAS and NPK (13:0:45) @ 1.5% at 40 DAS allowed for the observation of the maximum values.